(untitled) (Research, Society and Development, 2020)
Astrobiology involves the investigation of the origin, evolution and distribution of life in the universe. In the present study we investigate astrobiological subjects that can be taught in conjunction with the proposed curriculum of biology in Brazilian high schools. In this effort, we seek to identify common ground between astrobiology and biology by analysing the official curricular documentation. In addition to this, we briefly discuss some critical topics reported in the literature. From our results, we suggest that this new scientific field, astrobiology, can be used as an interdisciplinary/multidisciplinary tool for teaching biology, in such a way as to guide educators and facilitate the teaching-learning process.